KAJIAN POTENSI DAN PENGEMBANGAN KAWASAN WISATA COBAN RONDO SEBAGAI KAWASAN EKOWISATA KABUPATEN MALANG - Kogoya, Wes; Setyabudi, Irawan; Alfian, Rizki (Universitas Tribhuwana Tunggadewi, 2018)
Indonesia is an agrarian country with all its natural and cultural resources. Indonesia's strategic location is a major factor that is very influential on the development of the nation and state. Currently, tourism is growing rapidly along with the increasing number of visitors visiting. In addition, tourism is also an important sector for economic growth in Indonesia. In this research is done by collecting data by direct observation to the object to know the daily activities of the local community. The management in Coban Rondo area development as ecotourism. From the results of research on the potential assessment and development of Coban Rondo area as an ecotourism area of Malang Regency. Can be concluded in the form of sustainable development strategy of Coban Rondo natural tourist area. The main one is an aggressive management strategy that is a very profitable strategy because it addresses opportunities and strengths so that it can take advantage of existing opportunities in the form of local government policy in the implementation of natural ecotourism area management Coban Rondo. Indonesia merupakan negara agraris dengan segala potensi sumber daya alam dan budaya yang dimiliki. Letak Indonesia yang strategis merupakan faktor utama yang sangat berpengaruh pada pembangunan bangsa dan negara. Saat ini pariwisata berkembang pesat seiring meningkatnya jumlah wisatan yang berkunjung. Selain itu pariwisara juga merupakan sektor penting bagi pertumbuhan ekonomi di Indonesia. Dalam penelitian ini dilakukan dengan pengumpulan data dengan cara pengamatan langsung ke objek untuk mengetahui aktivitas sehari-hari masyarakat setempat. Pihak pengelola dalam pengembangan kawasan Coban Rondo sebagai ekowisata. Dari hasil penelitian tentang kajian potensi dan pengembangan kawasan Coban Rondo sebagai kawasan ekowisata Kabupaten Malang. Dapat di simpulankan berupa strategi pengembangan secara berkelanjutan kawasan wisata alam Coban Rondo. Yang utama yaitu strategi pengelolaan yang agresif yaitu strategi yang sangat menguntungkan karna menujukan peluang dan kekuatan sehingga dapat memanfaatkan peluang yang ada berupa kebijakan pemerintah daerah dalam pelaksanaan pengelolaan kawasan ekowisata alam Coban Rondo.